Respuesta :

Answer:

Step-by-step explanation:

We will apply the definition of the derivative. Then we use algebra to expand and simplify the numerator. Next, we can cancel a factor of

h

in the numerator and denominator since

h

is approaching zero but not actually equal to zero. Finally, we can simply substitute zero for

h

to evaluate the limit.

f

(

x

)

=

lim

h

0

f

(

x

+

h

)

f

(

x

)

h

=

lim

h

0

(

x

+

h

)

2

2

(

x

+

h

)

+

3

(

x

2

2

x

+

3

)

h

=

lim

h

0

2

x

h

2

h

+

h

2

h

=

lim

h

0

2

x

2

+

h

=

2

x

ACCESS MORE